Effects of temperature and nutrient regimes on the recruitment of laminaria digitata - Ruud, Hjalmar (2021)
Kelps are important macroalgae found in the temperate rocky marine habitats along the northern Atlantic Ocean coast. Kelp forests and its services to the ecosystem are globally at risk due to anthropogenic activity and climate change, by altering the temperature gradient and the nutrient input and where the kelps exist. This could be detrimental for the coming generations of the kelp, Laminaria digitata, which is one of the major kelp species in the north Atlantic Ocean. As of this, nutrients and temperature regimes that allow microscopic phases for gametogenesis and survival could be at risk. As gametophyte growth and sporophyte development have different optimal temperatures, the microscopic life phases develop at different rates when exposed to different environmental conditions. To investigate the effects of temperature and nutrient regimes on gametophyte growth, gametogenesis, and early sporophyte formation of L. digitata, two populations (Bodø and Quiberon) were exposed to four temperature regimes (4, 8, 12, 18o C) and two nutrient treatments (high (HN) and low(LN)) based on local data from each site. Bodø represents the intermediate zone, which might provide optimum conditions while Quiberon represent the southern distributional limit. The experiment followed a factorial design, testing all temperatures in both nutrient conditions through a mechanistic approach considering both sites. We hypothesized that the response of each population shows local adaptation relating to local nutrient and temperature histories. Results showed that the gametophytes of each population responded differently to the treatments, especially in respect to sporophyte formation, however had similar patterns for development in general. Sporophyte recruitment was 7% higher for the Quiberon population, however, both populations responded positively to optimal temperatures (8 and 12o C) in terms of ontogenetic development. Moreover, both populations interaction with temperature were significantly related to sporophyte recruitment, with Bodø also having a response to the nutrient treatment. In both populations, longer periods of increased temperatures (18o C) enhanced vegetative gametophyte growth but inhibited sporophyte production. This study provides an insight to how Laminaria digitata gametophytes responds to forced environmental conditions in terms of survival, growth, and recruitment. It shows distinct differences between populations, exhibiting local adaption based on local nutrient and temperature histories. With emphasis on which treatments results in the optimal conditions to further knowledge on the adaptation responses of the species to environmental conditions and climate change.